KAJIAN TENTANG PENGARUH KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN CIREBON - Yumanhadi Idris (JURISMA : Jurnal Riset Bisnis & Manajemen, 2015)
This study aims to determine the effect of job satisfaction and discipline to performance of employees in the department of population and civil registry district of Cirebon.This research is associative, which aim to determine the influence between two or more variables. Data was collected by means of the field study that interviews and quentionares, as well as library research by studying the books that have relevance to the problem studied, journals and reports available to the problem to be solved. The samples in this study were all employees of the department ofpopulation and civil registry Cirebon totaling 43 people.Based on the research results and the proposed hypothesis indicated that there is a positive and significant impact the job satisfaction on the performance of employees, this is evidenced by the value of t count > t table is 7,934 > 2,020 and significant value of 0,00< 0,05, which is partially job satisfaction on performance of employees to 60,6% and the remaining 39,4% is influence by other variables not examined. Then there is a positive and significant impact between disciplines on performance of employees, this is evidenced by the value t count > t table is 7,060 > 2,020 and significant value of 0,00 < 0,05, where the influence of the partial disciplines on performance of employees by 54,9% and the remaining 45,1% influenced by another variables not examined. And there is a positive and significant effect between job satisfaction and discipline together on performance of employees. This evidenced by the presence of F count > F table is 54,245 > 3,23Â  and where is the influence of job satisfaction and disciplines together onperformance of employees by 71,7% and the remaining 28,3% is influenced by variables another is not examined.Â Keywords : Job satisfaction, discipline and performance of employees